THE STIGMA OF INDONESIAN SOCIETY ON COVID-19 PATIENTS AND HEALTH WORKERS BASED ON THE HEALTH BELIEF MODEL THEORY - Aprianti Aprianti (Faculty of Public Health, Andalas University, 2021)
The number of covid-19 cases in Indonesia has increased significantly. So, the government recommend physical distancing. As a new disease, the policy caused the public worry. This triggers the community to give social stigma to Covid-19 sufferers and health workers. This research is a quantitative study with a cross sectional method. The Indonesian population aged 15 - 44 years, have access to the internet, not health workers, not students in health schools andÂ willing to be respondents. The number of samples was 360 respondents. Bivariate data analysis used chi square test and multivariate using logistic regression. As many as 63.6% of respondents did not know their Covid status. Respondents gave a stigma of 50.8%. The variables related to the stigma given by the community to health workers and Covid-19 patients were perception of severity (p value = 0.037), self-efficacy (p value = 0.016) and perceived threat (p value = 0.001). The variable with the most dominant relationship is perceived threat with the value of Exp (B) = 3, 834. It is hoped that the need for education from health workers to the community about the covid-19 virus and how to overcome it so that people do not feel threatened and give stigma.